A comprehensive model for cyber risk based on marked point processes and its application to insurance - Gabriela Zeller; Matthias Scherer (European Actuarial Journal, 2021)
After scrutinizing technical, legal, financial, and actuarial aspects of cyber risk, a new approach for modelling cyber risk using marked point processes is proposed. Key covariates, required to model frequency and severity of cyber claims, are identified. The presented framework explicitly takes into account incidents from malicious untargeted and targeted attacks as well as accidents and failures. The resulting model is able to include the dynamic nature of cyber risk, while capturing accumulation risk in a realistic way. The model is studied with respect to its statistical properties and applied to the pricing of cyber insurance and risk measurement. The results are illustrated in a simulation study.
Keywords: 510; Cyber risk; Cyber insurance; Emerging risks; Marked point processes; Accumulation risk